Landslide model tests with a miniature 2D principal stress sensor - Kun Fang; Yulei Fu; Huiming Tang; Tangzhe Gao; Pengju An; Qiong Wu (Journal of Rock Mechanics and Geotechnical Engineering)
Understanding the stress distribution derived from monitoring the principal stress (PS) in slopes is of great importance. In this study, a miniature sensor for quantifying the two-dimensional (2D) PS in landslide model tests is proposed. The fundamental principle and design of the sensor are demonstrated. The sensor comprises three earth pressure gages and one gyroscope, with the utilization of three-dimensional (3D) printing technology. The difficulties of installation location during model preparation and sensor rotation during testing can be effectively overcome using this sensor. Two different arrangements of the sensors are tested in verification tests. Additionally, the application of the sensor in an excavated-induced slope model is tested. The results demonstrate that the sensor exhibits commendable performance and achieves a desirable level of accuracy, with a principal stress angle error of ±5° in the verification tests. The stress transformation of the slope model, generated by excavation, is demonstrated in the application test by monitoring the two miniature principal stress (MPS) sensors. The sensor has a significant potential for measuring primary stress in landslide model tests and other geotechnical model experiments.